Feeding and defaecation behaviour of Triatoma patagonica (Del Ponte, 1929) (Hemiptera: Reduviidae) - Nattero, Julieta (2002)
Among the vectors of Chagas disease, Triatoma patagonica is a species in the process of adaptation to the human environment being recently registered in urban and suburban zones. However, its importance as a vector of Chagas disease is unknown. The aim of this work was to evaluate two aspects of vectorial competence: the feeding behaviour and the defaecation pattern. These processes were studied in females of T. patagonica fed ad libitum on a restrained pigeon. The results showed that the blood meal size was negatively correlated with the time of first defaecation (r = -0.42). The first defaecation was emitted before the first 10 min and defaecations during feeding were frequent. A total of 73% of females, defaecated during the first 30 min post-feeding. These results suggest that if this species subsequently colonizes the domicile, it would be capable of transmitting Trypanosoma cruzi.